Kanak-kanak minoriti orang asli di Malaysia: Menggapai literasi Bahasa Melayu - Shaari, Abdull Sukor; Yusoff, Nuraini; Ghazali, Mohd Izam; Dali, Mohd Hasani (2011)
Semai language is the native language for students at the Kampung Orang Asli Terisu Cameron Highlands, Pahang, Malaysia.In contrast, the Malay Language (BM) is the second language that is more significantly used in the classroom. The study was conducted to identify the main problems encountered in the Malay Language Literacy and the reasons for the problems.The study sample consisted of 33 Year Five Orang Asli students, two Malay language teachers in Sekolah Kebangsan Terisu, Cameron Highland, Pahang.This study used the qualitative research design of a case study through interviews as the research method.Based on the interviews, the findings showed that the main problem faced in the Malay Language literacy is closely related to cultural issues.The study is expected to provide input to the curriculum developers, education administrators and teachers.